THE IMPORTANCE OF PHARMACOMETRY ON DEVELOPING BIOLOGICAL PRODUCTS - Blandón Saborío, Karen (2023)
Pharmacometry is an interdisciplinary science that uses mathematical and statistical tools for data modeling, in order to support the development process of pharmaceutical products, as well as their safe and effective use. Biological drugs are all those that use biological sources as starting material; they are complex molecules and their pharmacokinetic modeling, as well as the set-up of safety and efficacy profiles, are complicated. This has been improved due to the current development of digital tools such as pharmacometric software, not only because they allow the optimization of treatments in the population, but also because they favor the identification of subpopulations with special characteristics. Thanks to this, the safety and efficacy of therapies is extended to people with atypical metabolizers, particular clinical cases, and drugs with a narrow therapeutic margin, in order to generate individualized dosage regimens. Although pharmacometry is an emerging branch of pharmacological knowledge, its robustness in the integration and prediction of data behavior positions it as a potential key piece in the future development of precision medicine and pharmacogenomics; even more so, if it is directed to the study of biological products. Key words: Biological Products, Therapeutic use, Pharmacometry, Individualization of Therapy. Source: DeCS/MeSH.